1978
DOI: 10.1111/j.1532-5415.1978.tb01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherol in Osteoarthritis: A Controlled Pilot Study

Abstract: Thirty-two patients entered a simple-blind, cross-over study on the action of tocopherol in osteoarthritis; only 3 did not complete the course. Each patient was randomly assigned either to the tocopherol group (600 mg/day for 10 days) or to the placebo group. After 10 days the groups were transposed. The analgesic and other possible effects of tocopherol vs. placebo were assessed by the patients' daily records, by the physician's personal examination and interview, and by observations on the use of an addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Our results differ from the study of Machtey and Ouaknine 11. Those authors found a 52% improvement in the group treated with vitamin E compared with 4% in the placebo group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differ from the study of Machtey and Ouaknine 11. Those authors found a 52% improvement in the group treated with vitamin E compared with 4% in the placebo group.…”
Section: Discussioncontrasting
confidence: 99%
“…Several clinical studies have found therapeutic benefits of α-tocopherol in the symptomatic treatment of RA9 10 and OA 11-13. Short term clinical trials with a small number of patients have suggested that vitamin E treatment may be more effective than placebo in relieving pain11 12 and may have similar efficacy to diclofenac 13…”
mentioning
confidence: 99%
“…There are several modalities that may play a role as conservative management for knee osteoarthritis, such as glucosamine, diacerine, and viscoelastic injection. In addition, some researchers have reported molecular targeting therapy, such as vitamin E and glutathione, in the role of the antioxidants to treat knee osteoarthritis (Machtey and Ouaknine 1978; Blankenhorn 1986; Jordan et al 2004). However, some reports have argued against these therapies in the treatment of knee osteoarthritis (Wluka et al 2002; Brand et al 2001), and these treatments remain controversial (Brand et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Two trials concluded that vit E was more efficient than placebo in decreasing pain. In a small 10-day single-blind crossover RCT on mainly spondylosis, 600 mg of vit E per day was superior to placebo as assessed by a patient questionnaire [71], whereas in a 6-week double-blind RCT on OA, 400 IU of α-tocopherylacetate once a day was superior to placebo as assessed by a joined patients' and doctors' global assessment of pain [72]. One trial suggested that vit E was no less efficient than diclofenac in decreasing pain.…”
Section: Resultsmentioning
confidence: 99%